2020
DOI: 10.1111/ppl.13223
|View full text |Cite
|
Sign up to set email alerts
|

Improving drought tolerance in rice: Ensuring food security through multi‐dimensional approaches

Abstract: Drought has been highly prevalent around the world especially in Sub-Saharan Africa and South-East Asian countries. Consistent climatic instabilities and unpredictable rainfall patterns are further worsening the situation. Rice is a C 3 staple cereal and an important food crop for the majority of the world's population and drought stress is one of the major growth retarding threats for rice that slashes down grain quality and yield. Drought deteriorates rice productivity and induces various acclimation respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 259 publications
(375 reference statements)
0
34
0
Order By: Relevance
“…The free hydroxyl groups of soluble sugars compensate that of water to maintain the protein structure and function as well as the hydrophilic interactions in the cell membrane (Poonam et al, 2016). Drought also incites the plant root system to take up the available water more efficiently and causes an increase in the root‐shoot ratio, which is invariably facilitated by transportation and accumulation of soluble sugars in the roots (Khan, Palakolanu, et al, 2020). Additionally, Du et al (2020) showed that increased sugar metabolism, transport, and distribution caused greater root‐shoot ratio, thereby enhancing drought tolerance.…”
Section: Sugar Status Impacts Source‐sink Relationship During Droughtmentioning
confidence: 99%
“…The free hydroxyl groups of soluble sugars compensate that of water to maintain the protein structure and function as well as the hydrophilic interactions in the cell membrane (Poonam et al, 2016). Drought also incites the plant root system to take up the available water more efficiently and causes an increase in the root‐shoot ratio, which is invariably facilitated by transportation and accumulation of soluble sugars in the roots (Khan, Palakolanu, et al, 2020). Additionally, Du et al (2020) showed that increased sugar metabolism, transport, and distribution caused greater root‐shoot ratio, thereby enhancing drought tolerance.…”
Section: Sugar Status Impacts Source‐sink Relationship During Droughtmentioning
confidence: 99%
“…Genetic engineering approaches offer viable opportunities for accelerated crop improvement (Khan et al, 2020;Lohani et al, 2020;Arya et al, 2021). Genes controlling traits, such as flowering time, disease resistance and lipid profile, have been identified and used as targets for soybean improvement (Haun et al, 2014;Arya et al, 2018;Ngaki et al, 2021).…”
Section: Genetic Engineeringmentioning
confidence: 99%
“…It can become chronic in climatic regions with limited water resources or in areas where rainfall is erratic (Tian and Lie 2006;Nawaz et al 2014;Khan et al 2020;Sehar et al 2020;Seleiman et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that hormonal signals crosstalk under drought condition (Khan et al 2020) may cooperate to govern drought stress responses , such as ethylene and ABA accumulation regulate many developmental processes and adaptive stress responses (Nazar et al 2015;Sehar et al 2020;Takahashi et al 2020). Drought stress rapidly induces the expression of 9-cis-epoxycarotenoid dioxygenase 3 (NCED3), which is important in ABA synthesis (Behnam et al 2013).…”
Section: Introductionmentioning
confidence: 99%